2021
DOI: 10.1016/j.scitotenv.2021.148905
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of SARS-CoV-2 genes in water reclamation facilities: From influent to anaerobic digester

Abstract: Several treatment plants were sampled for influent, primary clarifier sludge, return activated sludge (RAS), and anaerobically digested sludge throughout nine weeks during the summer of the COVID-19 pandemic. Primary clarifier sludge had a significantly higher number of SARS-CoV-2 gene copy number per liter (GC/L) than other sludge samples, within a range from 1.0 × 10 5 to 1.0 × 10 6 GC/L. Gene copy numbers in raw influent significantly correlated with gene copy n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 46 publications
0
7
0
2
Order By: Relevance
“…Pesquisas procedidas em plantas de tratamento de esgoto em escalas reais, entretanto, demonstraram que a remoção de fragmentos do genoma viral do SARS-CoV-2 tem sido insuficiente nas etapas de sedimentação primária SERRA-COMPTE et al, 2021). Dessa forma, embora o processo de sedimentação primária seja considerado como extremamente importante na remoção de uma porção significativa das partículas viras do SARS-CoV-2 em esgotos (BHATTARAI et al, 2021), a remoção completa do novo coronavírus no tratamento dessas matrizes tem requerido a aplicação de outros processos de tratamento.…”
Section: Sedimentação Primáriaunclassified
See 1 more Smart Citation
“…Pesquisas procedidas em plantas de tratamento de esgoto em escalas reais, entretanto, demonstraram que a remoção de fragmentos do genoma viral do SARS-CoV-2 tem sido insuficiente nas etapas de sedimentação primária SERRA-COMPTE et al, 2021). Dessa forma, embora o processo de sedimentação primária seja considerado como extremamente importante na remoção de uma porção significativa das partículas viras do SARS-CoV-2 em esgotos (BHATTARAI et al, 2021), a remoção completa do novo coronavírus no tratamento dessas matrizes tem requerido a aplicação de outros processos de tratamento.…”
Section: Sedimentação Primáriaunclassified
“…O processo conduzido em aerobiose tem se baseado na utilização de tanques aerados que promovem a atividade de consórcios bacterianos que degradam a matéria orgânica existente nos efluentes na presença de oxigênio livre. Já o processo, quando conduzido em anaerobiose, tem se utilizado de biorreatores que promovem a metabolização da matéria orgânica dos efluentes na ausência de oxigênio livre, além de serem também utilizados para estabilizar o lodo residual gerado nos tratamentos aeróbios, consequentemente reduzindo a quantidade de biomassa produzida nas unidades biológicas (MOHAN et al, 2021;BHATTARAI et al, 2021). As unidades biológicas também têm incluído processos de sedimentações secundárias, capazes de adsorver, aglomerar e reter os compostos orgânicos e sólidos suspensos em lodos residuais (TOPARE et al, 2011;BOGLER et al, 2020).…”
Section: Processos Biológicosunclassified
“…The prevalence of the SARS-CoV-2 or its genetic material in the environmental materials, especially wastewater samples collected from treatment plants and air samples from the built environment have been well documented in many countries, including the USA ( Nemudryi et al, 2020 , Peccia et al, 2020 , Sherchan et al, 2020 , Palmer et al, 2021 ), Spain ( Randazzo et al, 2020 , Balboa et al, 2021 ), Turkey ( Kocamemi et al, 2020a , Kocamemi et al, 2020b ), Netherlands ( Medema et al, 2020 ), Saudi Arabia ( Hong et al, 2021 ), Australia ( Ahmed et al, 2020 ), Japan ( Haramoto et al, 2020 , Hata et al, 2021 ), Iran ( Gholipour et al, 2021 , Tanhaei et al, 2021 ), Czech Republic ( Mlejnkova et al, 2020 ), India ( Chakraborty et al, 2021 , Kumar et al, 2021a ), France ( Trottier et al, 2020 , Wurtzer et al, 2021 ), United Arab Emirate (Hasan et al, 2020), Germany ( Westhaus et al, 2021 ), Israel ( Abu Ali et al, 2021 ), and Italy (La Rosa et al, 2020; Rimoldi et al, 2020 ). Similarly, some treated effluents have also been reported to contain the SARS-CoV-2 RNA ( Ampuero et al, 2020 , Abu Ali et al, 2021 , Bhattarai et al, 2021 , Carrillo-Reyes et al, 2021 , Graham et al, 2021 ). Although some treatment techniques are highly effective in removing the virus and its genetic material in the wastewater treatment plants (WTTPs) (Hasan et al, 2020; Balboa et al, 2021 , Sherchan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the ecological and health risks concern of inappropriate use of reclaimed wastewater and sewage sludge have been recently intensified on their potential escalation of COVID-19 among the wastewater workers and farmers, including in the urban settings ( Adelodun et al, 2020b , Adelodun et al, 2020c , Adelodun et al, 2021b ; Ali et al, 2021; Brisolara et al, 2021 , Dada and Gyawali, 2021 , Zaneti et al, 2021 ). It has also been demonstrated that enveloped virus could survive for days in the water environment, depending on the environmental conditions ( Bivins et al, 2020 , Hokajärvi et al, 2021 , Shao et al, 2021 , Wurtzer et al, 2021 ), or treatment processes ( Bhattarai et al, 2021 , Carrillo-Reyes et al, 2021 , Kumar et al, 2021a ). Thus, consequently enters the surface and groundwater sources via leaking sewers, runoff, or land application of untreated sewage sludge, thereby leading to transmission by ingestion of such virus-contaminated water resources ( Adelodun et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%
“…Mina Aghababaei | Biomed J Sci & Tech Res | BJSTR. MS.ID.007537.Volume 47-Issue 4 DOI: 10.26717/BJSTR.2022.47.007537 38758The impact of various wastewater treatment technologies on microorganisms has been extensively investigated[4][5][6][7][8][9][10][11][12][13][14][15]. However, SARS-CoV-2 presented unique possibilities.…”
mentioning
confidence: 99%